The Adoption of Crowdfunding by Indonesia's Political Party: A Case Study on Partai Solidaritas Indonesia - Savanid Vatanasakdakul; Muhamad Fatih Azka (Jurnal Studi Pemerintahan, 2021)
This paper offers an analysis of crowdfunding adoption by a political party in explore the phenomenon of crowdfunding for political causes, which is an under-researched topic, and provide a new contribution to knowledge that raises awareness of the potential and challenges of adopting crowd funding by a political entity in Indonesia, which is Partai Solidaritas Indonesia (PSI). By having a case study on PSI adoption of crowdfunding, this paper analyses PSI crowdfunding campaigns’ effectiveness, strength, and weaknesses. It also draws an analysis on the implications of this funding model beyond political votes. The findings suggest that although KitaBisa was created for crowdfunding campaigns with social purposes, PSI’s political campaigns inKitaBisa gained more funds than its social campaigns. However, the overall success rate of PSI political crowdfunding campaigns is very low. Despite ahigh level of social mediaengagement, its campaigns lack coordination.